(untitled) (Research, Society and Development, 2022)
Objective: Demonstrate, through an Interactive Literature Review, care strategies for elderly patients with Benign Prostatic Hyperplasia (BPH). Methods: This is an Integrative Literature Review (RIL) study, with data collection through online access in Cochrane Library databases and databases; PubMed, Cochrane Library and VHL. After evaluating and synthesizing the articles, the data were analyzed using the IraMuTeQ software, presenting the results through the similarity analysis with the identification of co-occurrences between the words and indications of the connection. Results/Discussion: From the results obtained through the co-occurrence tree, 3 classes were divided: The prevalence of the relationship between HBP and LUTS as a way of detecting diseases; Evaluation of the elderly population with BPH as a way to identify limitation, cause or condition that reduces the effectiveness and effect of the treatment.; Interventions for BPH symptoms in the elderly. Conclusion: It is observed that care strategies for elderly people with Benign Prostatic Hyperplasia are still scarce, limiting pharmacological and behavioral interventions. The assessment of the specificities of this population is presented as a way to monitor the results from the treatments, in addition to adverse effects related to avoiding the worsening of the condition.